Monoclonal antibody or aspirin desensitization in NSAID-exacerbated respiratory disease (N-ERD)? - Van Broeck, Dorien; Steelant, Brecht; Scadding, Glenis; Hellings, Peter W. (Frontiers in Allergy, 2023)
Manuscript will be a part of the whole article. Abstract of Frontiers in Allergy about this research topic: Nonsteroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (NERD) is a clinical syndrome characterized by nasal polyposis, asthma, and intolerance to aspirin /NSAID. It affects approximately 15% cases of severe asthma, 10% of nasal polyps and 9% of rhinosinusitis. NERD results in associated asthma exacerbation, oral corticosteroids bursts, corticosteroid-dependent disease, and multiple endoscopic sinus surgeries. NERD is characterized by an imbalance in eicosanoid levels, especially CysLTs, PDG and PGE2. The release by mast cells, eosinophils, platelets cause the epithelial release of IL-33 and TSLP and these cytokines activate innate lymphoid cell type 2 (ILC2). Patients with NERD present nasal symptoms (congestion, hyposmia/anosmia, nasal discharge) and lower airways symptoms (cough, sneezing, shortness of breath, chest tightness), anosmia, severe hyposmia as well as severe asthma which impacts the quality of life in this disease and leads to safety concerns in patients daily lives. Despite the variety of treatment strategies, the likelihood of recurrence of symptoms is high in patients with NERD. The most important strategies for treating NERD are listed as following: drug therapies, aspirin desensitization, monoclonal antibodies and other therapies associated. NERD treatment remains a major challenge in the current situation. Selecting the appropriate patient for aspirin desensitization, monoclonal antibodies or both is essential. This review provides an overview on aspirin desensitization and biologics in N-ERD and might help in decision making from both the perspective of the physician and patient. Patient characteristics, safety, efficacy, health care costs, but also patient preferences are all factors to take into account when it comes to a choice between biologics or aspirin desensitization.